2011
DOI: 10.1103/physreve.84.021303
|View full text |Cite
|
Sign up to set email alerts
|

Effect of particle size on energy dissipation in viscoelastic granular collisions

Abstract: We analyze the scaling properties of the Hertz-Kuwabara-Kono (HKK) model, which is commonly used in numerical simulations to describe the collision of macroscopic noncohesive viscoelastic spherical particles. Parameters describing the elastic and viscous properties of the material, its density, and the size of the colliding particles affect the restitution coefficient ɛ and collision time τ only via appropriate rescaling but do not change the shape of ɛ(v) and τ(v) curves, where v is the impact velocity. We ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Note that these model parameters may also depend on the particle size. Actually, the effect of the particle size on the CoR has not been studied a lot despite the fact that its value may have a significant impact on DEM results [45,50]. In this work, a few additional experiments with different sized low carbon steel spheres were carried out, which revealed that the particle size does affect the value of μ but barely that of n l .…”
Section: Model Developmentmentioning
confidence: 84%
“…Note that these model parameters may also depend on the particle size. Actually, the effect of the particle size on the CoR has not been studied a lot despite the fact that its value may have a significant impact on DEM results [45,50]. In this work, a few additional experiments with different sized low carbon steel spheres were carried out, which revealed that the particle size does affect the value of μ but barely that of n l .…”
Section: Model Developmentmentioning
confidence: 84%
“…In the following DEM simulations, the simplified Hertz Mindlin contact model without microslip and with damping as described by Tsuji et al [17], and Antypov et al [1], will be used. In normal direction of the contact, the Hertz model is as follows:where is the equivalent Young modulus of the contact, is the equivalent contact radius and is the overlap in normal direction.…”
Section: Stress-dependent Friction Coefficientmentioning
confidence: 99%
“…In the proposed model each contact is treated individually. After the computation of normal and tangential force for each contact, the damping is applied as described by Tsuji et al [17], and Antypov and Elliott [1]. …”
Section: Stress-dependent Friction Coefficientmentioning
confidence: 99%
“…The term "effective mass" already have been used by Stronge (2000), Dintwa, (2006), Bordbar, Hyppänen (2007), Antypov, Elliott, Hancock (2011), and by many others authors. Also the mass m was called like the reduced mass by Landau (1944), Brilliantov (1996.…”
Section: Remarkmentioning
confidence: 99%